2016
DOI: 10.17221/8681-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical, haematological and oxidative stress responses of common carp (Cyprinus carpio L.) after sub-chronic exposure to copper

Abstract: ABSTRACT:The aim of the present study was to investigate the impact of copper-based pesticides (at concentrations of copper of 20, 30, 40 and 70 µg/l) on one-year-old common carp (Cyprinus carpio L.) during 28 days of exposure. Abnormal behaviour was observed in fish exposed to 70 µg/l from Day 14. Histological alterations were noticed only in liver in the groups exposed to 40 and 70 µg/l. Significant changes (P ˂ 0.05) in almost all haematological indices were found, especially in the group exposed to the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 81 publications
1
17
0
Order By: Relevance
“…Among metal ligands, induced MTs are involved in non-enzymatic homeostasis and a detoxifi cation mechanism of fi sh against metal exposure. In previous studies, the induction of MT content in fi sh gills exposed to metals has been documented in tilapia (Oreochromis mossambicus) [43][44], common carp (Cyprinus carpio) [45][46], and catfi sh (Clarias gariepinus) [47]. Our study also demonstrated that waterborne exposure to Cu 2+ could increase MT contents in gills of C. auratus in a concentration-dependent manner, confi rming that MT synthesis level in C. auratus gills is a sensitive biomarker for aquatic pollution of metals.…”
Section: Discussion Of Resultsmentioning
confidence: 96%
“…Among metal ligands, induced MTs are involved in non-enzymatic homeostasis and a detoxifi cation mechanism of fi sh against metal exposure. In previous studies, the induction of MT content in fi sh gills exposed to metals has been documented in tilapia (Oreochromis mossambicus) [43][44], common carp (Cyprinus carpio) [45][46], and catfi sh (Clarias gariepinus) [47]. Our study also demonstrated that waterborne exposure to Cu 2+ could increase MT contents in gills of C. auratus in a concentration-dependent manner, confi rming that MT synthesis level in C. auratus gills is a sensitive biomarker for aquatic pollution of metals.…”
Section: Discussion Of Resultsmentioning
confidence: 96%
“…Abarghoei et al [32] treated the gold fish to silver sulphate, the lymphocyte count decreased at 24 and 48 hours exposure period and increased in 96 hours, but the results of monocytes counts showed significant similarities. Sevcikova et al [33]in the blood of common carp (Cyprinuscarpio)and Hedayati and Darabitabar [34] in Caspian roach (Rutilusrutilus) observed significantly greater lymphocyte reduction at the highest concentration of copper whereas monocyte and neutrophil counts increased as compared to the control group. The present studies indicate that exposure to lead alters the leucocyte counts in fish, H. fossilis when exposed to lead.…”
Section: Discussionmentioning
confidence: 99%
“…Selected liver tissues were prepared for histopathology. Tissues were fixed in buffered 10% neutral formalin, dehydrated, embedded in paraffin and sectioned on a microtome at thickness of 4 μm and stained with hematoxylin and eosin [26,44].…”
Section: Methodsmentioning
confidence: 99%